2017
DOI: 10.1186/s12941-017-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm and metallo beta-lactamase production among the strains of Pseudomonas aeruginosa and Acinetobacter spp. at a Tertiary Care Hospital in Kathmandu, Nepal

Abstract: Introduction Pseudomonas aeruginosa and Acinetobacter spp. are found to be associated with biofilm and metallo-β-lactamase production and are the common causes of serious infections mainly in hospitalized patients. So, the main aims of this study were to determine the rates of biofilm production and metallo beta-lactamase production (MBL) among the strains of Pseudomonas aeruginosa and Acinetobacter spp. isolated from hospitalized patients.MethodsA total of 85 P. aeruginosa isolates and 50 Acinetobacter spp. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
8
7
2
Order By: Relevance
“…Similar to other studies, our findings showed very high rates of biofilm formation in XDR A. baumannii strains [24], and this phenomenon is associated with protective properties of persistent cells in the biofilms,and could be a result of inadequate penetration of antimicrobial agents into the biofilms [24, 25]. Our study results showed a statistically significant association between antimicrobial resistance phenotypes and biofilm formation, which was in line with other findings [9, 24], but it was in contrast to results of the study by Baniya et al [25]. A. baumannii strains formed strong biofilm were endemic in respective hospitals, indicating that microbial cells grown in biofilms are more resistant to different environmental stress conditions [24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other studies, our findings showed very high rates of biofilm formation in XDR A. baumannii strains [24], and this phenomenon is associated with protective properties of persistent cells in the biofilms,and could be a result of inadequate penetration of antimicrobial agents into the biofilms [24, 25]. Our study results showed a statistically significant association between antimicrobial resistance phenotypes and biofilm formation, which was in line with other findings [9, 24], but it was in contrast to results of the study by Baniya et al [25]. A. baumannii strains formed strong biofilm were endemic in respective hospitals, indicating that microbial cells grown in biofilms are more resistant to different environmental stress conditions [24].…”
Section: Discussionsupporting
confidence: 90%
“…This resistance could result from modification of Lipopolysaccharide (LPS) at outer cell envelope, but identification of mechanism of colistin resistance in these isolates was beyond scope of our study [23]. Similar to other studies, our findings showed very high rates of biofilm formation in XDR A. baumannii strains [24], and this phenomenon is associated with protective properties of persistent cells in the biofilms,and could be a result of inadequate penetration of antimicrobial agents into the biofilms [24, 25]. Our study results showed a statistically significant association between antimicrobial resistance phenotypes and biofilm formation, which was in line with other findings [9, 24], but it was in contrast to results of the study by Baniya et al [25].…”
Section: Discussionsupporting
confidence: 82%
“…(26.31%) and Acinetobacter spp. (20.63%) as the major MBL producers which are in conformity with the data of Kaur et al (34.8%), Anuradha et al (28.57%) and Baniya et al (22%) for the respective organisms [18, 20, 31]. The coexistence of biofilm along with both beta-lactamases producing strains was found to be 2.87%.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, among a total of 82 isolates of P. aeruginosa, 22(26.3%) were biofilm-producer and this finding is comparable with other studies which show (27.05%) [20], (32.3%) [21] and (33%) [22], but in contrast with others who showed higher rate of biofilm production (73.68%) [12] and (83.33%) [23]. This variation in the rate of isolation also may be due to sample size, type of specimen studied because medical devices were frequently colonized by biofilm-forming organisms and the various methods used for biofilm identification like Congo red agar method or Tissue culture plate which were showing a higher rate of detection.…”
Section: Discussionsupporting
confidence: 92%
“…It was similar to another study [26] but the contrast study done by Dumaru et al [12]. No statistically significant association could be established between MBL production and biofilm production (Statistically insignificant, p=0.19) which was in agreement with another study [20]. The resistance to antimicrobials in biofilm-producer may be explained by the fact like, there are an increased plasmid transfer and gene transfer among biofilm bacteria which further intensifies the problem of drug resistance [27] and also by the fact that in the process of biofilm development, drug resistance varies bacterium to bacterium [28].…”
Section: Discussionsupporting
confidence: 92%